ChemInform Abstract: Synthesis and Biological Evaluation of 4‐Arylphthalazones Bearing Benzenesulfonamide and Anti‐Inflammatory and Anticancer Agents. Issue 42 (1st October 2013) - Yaseen, Shafiya; Ovais, Syed; Bashir, Rafia; Rathore, Pooja; Samim, Mohammed; Singh, Surender; Nair, Vinod; Javed, Kalim
Abstract The synthesized compounds are tested for their anti‐inflammatory and anticancer activities.